2005
DOI: 10.1167/iovs.05-0280
|View full text |Cite
|
Sign up to set email alerts
|

M Cells in the Follicle-Associated Epithelium of the Rabbit Conjunctiva Preferentially Bind and Translocate Latex Beads

Abstract: This study demonstrates that the follicle-associated epithelium of the rabbit conjunctiva contains a cell with morphologic characteristics and the ability to bind and translocate latex beads, which make it indistinguishable from antigen sampling M cells in the rabbit cecum and tonsils. Consistent with its hypothesized antigen sampling role, beads that have been translocated by this cell are rapidly transferred to cervical lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…Ex vivo experiments to examine microparticle transcytosis in rabbit conjunctival lymphoepithelium revealed that with incubation times as short as 20 min at 37 C, a greater number of microparticles were present within the submucosa compared to epithelial regions. Slowing transcytosis by incubation at 4 C; however, resulted in a greater number of beads within apical lymphoepithelium (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Ex vivo experiments to examine microparticle transcytosis in rabbit conjunctival lymphoepithelium revealed that with incubation times as short as 20 min at 37 C, a greater number of microparticles were present within the submucosa compared to epithelial regions. Slowing transcytosis by incubation at 4 C; however, resulted in a greater number of beads within apical lymphoepithelium (Liu et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…6B, 7). Others have reported the presence of M cells in conjunctival mucosa in several species, including rabbit, guinea pig, and canine (26,(40)(41)(42). M cells in the guinea pig conjunctiva were located in follicle-associated epithelium and showed variably sized microvilli (100 nm-1 mm), in contrast to epithelial cells (350 nm) (26,43).…”
Section: Discussionmentioning
confidence: 98%
“…6Bd, arrow, and 6Be) and clusters of cells with more rounded tops and straighter microvilli, which were observed only in conjunctiva goblet cells (Fig. 6Bd, arrowhead, and 6Bf) (26,27). TEM analysis after the binding of HRP-conjugated UEA-1 Ab (DAB reacted) showed a typical morphology of UEA-1 2 conjunctival epithelial cells following eyedrop administration of OVA plus CT (Fig.…”
Section: Eyedrop-administered Ag Passes Into the Nasal Cavity Minimalmentioning
confidence: 90%
“…Instead of the common laboratory species, mice, rats, and guinea pigs, we elected to use rabbits as the working animal model, bearing in mind that (i) numerous similarities between rabbit and human OMIS exist (13,66,67); (ii) several T-cell-mediated ocular surface diseases, including herpetic conjunctivitis and recurrent corneal herpetic stromal keratitis (HSK), have been reported to be similar in rabbits and humans, making it the most relevant animal model for exploring these human eye disorders (53,55,80); (iii) compared to mice and rats, rabbit CALT more closely resembles human CALT (23,25,28,44); (iv) microanatomy and immunohistological studies indicate that rabbit conjunctival mucosa is comparable to that of humans and has a typical follicular ultrastructure with an abundance of "conjunctival lymphoid follicles," whereas no lymphoid tissue was identified in mice and rats (28,42,43,47,84); (v) from a practical standpoint, unlike mice, rats, and guinea pigs, rabbits possess a relatively large conjunctival surface, offering abundant mucosa-associated lymphoid tissue for in vitro studies; and (vi) the recent availability of many monoclonal and polyclonal antibodies specific to rabbit immune cell CD markers, cytokines, and growth factors provide useful immunological tools for an unprecedented phenotypic and functional analysis of rabbit T-cell repertoire and function.…”
Section: Cd25mentioning
confidence: 99%